National Legislative and Regulatory Activities (OECD Publishing, 2012)
Argentina Amendment to the Criminal Code (2004) Australia Australian Nuclear Science and Technology Organisation (ANSTO) Amendment Act (2006) Commonwealth Radioactive Waste Management Legislation Amendment Act (2006) Finland Amendments to the Radiation Act and Radiation Decree (2005) France Decree on Securing Financing for Nuclear Charges (2007)Decree Licensing the Construction of the Basic Nuclear Installation "Flamanville 3" Comprising an EPR Reactor (2007) Germany Amendment to the Act on Preventive Radiation Protection (2006) Administrative Provisions on the Supervision of Environmental Radioactivity (2006)Ordinance on Radioactive Drugs (2007) Amendment to the Ordinance on the Treatment of Foodstuffs with Radiation (2006) European Agreement Relating to the International Transportation of Dangerous Goods by Road (ADR) (2006)Ordinance on the Transportation of Dangerous Goods by Road and Rail (2006)Ordinance to Amend the RID Regulations (2006) Ordinance on the Transportation of